How the Distribution of After-Tax Income Changed over the 1990s Business Cycle: A Comparison of the United States, Great Britain, Germany and Japan - Richard V. Burkhauser; Takashi Oshio; Ludmila Rovba (Deutsches Institut für Wirtschaftsforschung (DIW), 2007)
Using kernel density estimation we find that over their 1990s business cycles the entire distribution of after-tax (disposable) income moved to the right in the United States and Great Britain while inequality declined. In contrast, Germany and Japan experienced less growth, a rise in inequality and a decline in the middle mass of their distributions that spread mostly to the right, much like the United States over its 1980s business cycle. Inequality fell within the older population in all four countries and within the younger population in the United States and Great Britain, but rose substantially in Germany and Japan.
Keywords: D3; 330; income inequality; kernel density estimation; economic well-being; cross-country comparisons